P105. Network dynamics engaged in the modulation of motor behavior in chronic stroke patients - Pool, E.-M.; Kutscha, M.; Binder, E.; Eickhoff, S.B.; Fink, G.R.; Grefkes, C. (Clinical neurophysiology, 2015)
Affected hand movements are associated with a successive increase of neural activity in both hemispheres in the first weeks after stroke, which then return to levels observed in healthy controls, particularly in patients making full motor recovery. Little is known about the changes of the interplay of brain regions that enable the modulation of motor performance after stroke. In healthy subjects, an important feature of faster hand movements is mediated by a more effective coupling between distinct cortical and subcortical motor areas. But the mechanisms underlying the dynamic modulation of motor behavior in stroke patients related to motor impairment and recovery thereof are still unclear. We, therefore, investigated 10 chronic stroke patients with mild to moderate unilateral hand motor deficits and 10 healthy, age-matched controls by using functional magnetic resonance imaging (fMRI). Motor system activity was assessed by fist closures at different movement frequencies (0.5Hz, 1.0Hz, and 2.0Hz) performed with the affected/right or unaffected/left hand. When chronic stroke patients moved their affected, right hand, the fMRI data revealed a stronger frequency-dependent increase of neural activity within both the dorsolateral premotor cortex (PMd) and the superior parietal lobe (SPL), contralateral to the lesioned hemisphere as compared to healthy controls. Our findings suggest a critical contribution of contralateral PMd and SPL in the flexible adaption of the brain to varying motor demands in chronic stroke patients controlling temporal and spatial preciseness of recovered complex hand movements in the contralesional hemisphere.